Inferring geothermal heat flux from an ice-borehole temperature profile at Law Dome, East Antarctica. Issue 257 (22nd June 2020) - Mony, Laura; Roberts, Jason L.; Halpin, Jacqueline A.
Abstract: Geothermal heat flux (GHF) is an important control on the dynamics of Antarctica's ice sheet because it controls basal melt and internal deformation. However, it is hard to estimate because of a lack of in-situ measurements. Estimating GHF from ice-borehole temperature profiles is possible by combining a heat-transfer equation and the physical properties of the ice sheet in a numerical model. In this study, we truncate ice-borehole temperature profiles to determine the minimum ratio of temperature profile depth to ice-sheet thickness required to produce acceptable GHF estimations. For Law Dome, a temperature profile that is within 60% of the local ice thickness is sufficient for an estimation that is within approximately one median absolute deviation of the whole-profile GHF estimation. This result is compared with the temperature profiles at Dome Fuji and the West Antarctic Ice Sheet divide which require a temperature profile that is 80% and more than 91% of the ice thickness, respectively, for comparable accuracy. In deriving GHF median estimations from truncated temperature profiles, it is possible to discriminate between available GHF models. This is valuable for assessing and constraining future GHF models.